Korean science and technology in an international perspective - Pascha, Werner; Mahlich, Jörg (Physica-Verlag HD, 2012)
South Korea has attained spectacular economic success in recent decades. It has reached the status of a Newly Advanced Economy, with challenges increasingly mirroring those faced by other advanced economies. These include the necessary upgrading of the labor force, the frictions of switching to a national system of innovation adapted to leadership in R&D, market-based economic policies that reflect the government's difficulties in foreseeing future technological developments, and the consequences of social change for the innovation system and policy-making. In the forthcoming book the parallel challenges for innovation and technology for the Republic of Korea and other advanced economies will be analyzed more thoroughly with an international perspective in mind. This comparison and international benchmarking will allow policy makers and scholars to better appreciate how much the country has already moved into the circle of globally leading economies and what can be done to consolidate and strengthen its position.